SYSTEMATIZATION OF THE NURSING ASSISTANCE TO A CHILD AFFECTED BY GUILLAIN-BARRÉ SYNDROME. - Silva, Maria Elizabete Amorim; Dativo, Vanessa Lopes Maia; Araújo, Yana Balduíno; Silva, Kenya de Lima; Collet, Neusa (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2012)
Objective: to systematize the nursing assistance using the International Classification for Nursing Practice (ICNP®) with a child affected by Guillain-Barré Syndrome (SGB). Method: this is a case study carried out in the paediatric clinic of a public hospital in Paraiba, Brazil, on May 2011. The data were collected through an instrument considering the anamnesis, the physical examination, and data recorded in the medical records. The ICNP® version 1.0 was used to determine the diagnoses, results, and nursing interventions. The study was approved by the Research Ethics Committee of the hospital, under the Protocol 222/09. Results: four nursing diagnoses were identified, for which interventions were planned and implemented: impaired nutrition; productive cough; impaired walking; and low interactive behaviour. Conclusion: the systematization of the nursing assistance, using the ICNP®, allowed a greater organization and efficiency in the provision of care, offering an individual, holistic, and humanized care, taking into consideration the health-disease process and the reactions from the child-family binomial when facing hospitalization.